PERANAN KARAOKE DALAM KEHIDUPAN ORANG JEPANG - , MELINDA SABARINI; , Dr. Tatang Hariri, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The thesis examines karaoke in the life of the Japanese. Karaoke is recordings of music accompaniment without vocals, in which the vocal sounds will be vocalized by people singing outside the recordings by using microphones. Karaoke is one of the recreational of the Japanese leisure activities. Karaoke is not just a recreational activity, but is also used to smooth the business. From year to year the karaoke continues to innovations in technology, so it can be used in a variety of uses..Karaoke is a product of the music in Japan, making the karaoke as a part of the cultural elements that possess roles in the lives of the Japanese. What will be discussed in this thesis are the roles possessed by karaoke in lifes of the Japanese. Primary data in this paper are obtained by using the literature method. Based on the result of the research, it is determined that karaoke has four roles in the lives of the Japanese. The first role, it serves as an entertainment and stress relievers. Second, karaoke serves as a mean in expressing oneself. Third, karaoke serves as a mean of social interaction in the lives of the Japanese. And then, fourth, karaoke has a role in the world of health in Japan as one of the therapeutic media in hospitals. Karaoke is not simply as the Japaneseâs leisure activity, but it also has roles in the lifes of the Japanese.